Three keys to mission: Kingdom, incarnation and discipleship. (March 2015) - Robinson, Gareth
Through reflective practice, Glo Church has identified and used three keys to mission: declaring God's kingdom as part of the missio Dei ; incarnating the gospel individually and corporately; and offering support and challenge as the basis for discipleship.